Causal relationship between the volatility of stock market and selected macroeconomic variables: case of Malaysia - Lida Nikmanesh; Abu Hassan Shaari Md Nor; Tamat Sarmidi; Hawati Janor (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study examines the dynamic relationship between the volatility of stock market and macroeconomics’ volatility in Malaysia during the period of February 1991 to February 2013. For this purpose, monthly data on the KLCI stock index and a set of macroeconomic variables are used. Firstly, in order to estimate the volatility of each series, the well-known GARCH family models are employed. The empirical stylized facts in the stock indices and the macroeconomic variables are presented. Secondly, in order to investigate the causation between variables, the Toda and Yamamoto causality test through a VAR method is conducted using the volatility of stock market and macroeconomic variables. In addition, from the VAR, we generate Impulse Response Function and Variance Decomposition to track the evolution of economic shocks through the system. The result of this study shows that exchange rate volatility affects Malaysian stock market volatility considerably. Furthermore, trade openness is able to affect stock market volatility in Malaysia. These results will provide more precise information for investors, hedgers, managers and policy makers.